(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The application of knowledge derived from behavioral sciences to the design and improvement of public policy is a growing trend worldwide. In this context, nudges and libertarian paternalism concentrate a significant part of the attention, having shaped administrative practices at different levels of government. This text aims to present notes on emerging issues involving nudges and libertarian paternalism. Five topics are more carefully examined, presenting criticisms, counter-criticisms and conceptual extensions: 1) the tension between influence and manipulation, 2) the idea that nudges “infantilize” choosers, 3) differences and similarities between coercive paternalism and libertarian paternalism, 4) sludges and sludge audits, 5) the recently proposed idea of self-nudging. At the end, brief comments are made about the possibilities and challenges for these topics – originally addressed by the perspective of behavioral economics – to be thought from a behavior-analytic viewpoint.